Mercado educacional: a educação financeira como vantagem competitiva - Souza, Naiara Fernandes Abreu de (2021)
The Educational Marketing in Brazil represents a growing trend, which leads to increase competition and price war making essential the creation of new niches of activity and innovative solutions as competitive advantage. Furthermore, parents are progressively interested in schools that are able to offer personalized, experiential and competence-focused learning, indicating new opportunities to be explored. Considering that and also the new Common National Curriculum Base (BNCC), that this study intended to understand the opportunities behind the offer of Financial Education by private schools in Uberlândia as a potential competitive advantage. For this, a qualitative, multi-case research was carried out through semi-structured interviews with ten managers who represented eight of the main schools in Uberlandia. The saturation level was reached with the sample studied and data interpretation was made based on the content analysis technique. The results obtained indicate that Financial Education can be useful as a competitive differential in the private education sector since it makes up the parents' demand for Education in the 21st century and contributes to Educational Marketing of schools organizations. One mapping of challenges and opportunities regarding the implementation of the BNCC as well as some prospects of services related to Financial Education were also part of this study's deliverables.